Effectiveness of the motivational interviewing techniques with perpetrators of intimate partner violence: a non-randomized clinical trial - Cunha, Olga Cecília Soares (2023)
The effectiveness of perpetrators’ intervention programs (PIPs) remains controversial. Readiness and motivation for change are associated with treatment success among intimate partner vio-lence (IPV) perpetrators. In this study, we aimed to verify whether adding Motivational Interviewing Techniques (MIT) during the intake phase of a standard PIP (SPIP) increases treatment adher-ence. We also sought to evaluate the effectiveness of the MIT plus SPIP concerning an SPIP alone. In this non-randomized clinical trial, 50 participants were assigned to one of the two conditions SPIP alone or MIT plus SPIP. Data were collected at baseline and the end of the intervention. Proximal outcomes (dropout, inter-vention dose, motivation, attitudes toward IPV, problem-solving skills) and final outcomes (IPV perpetration, risk of IPV) were assessed. The Reliable Change Index (RCI) was also computed. Results indicated that SPIP plus MIT participants concluded the curriculum in a more advanced stage of change, revealed more readiness to change, evidenced greater clinical improvements, and displayed higher reductions in attitudes toward IPV, IPV perpetration, and recidivism risk than SPIP participants. These findings point to MIT’s ability to promote readiness to change and progression into the stages of change, enhancing interven-tion efficacy with IPV perpetrators. (NCT05484440)